Penerapan Algoritma Certainty Factor pada Metode Case-Based Reasoning untuk Sistem Pakar Deteksi Stunting - I Gede, Wiryawan; Wiryawan, I Gede; Yuwita, Kirana; Kurniasari, Arvita Agus (Jurnal Pekommas, 2024)
Stunting is a severe problem that significantly impacts future generations' growth and the quality of Human Resources (HR). In addition to the under-five age factor, stunting is also influenced by several interrelated factors. This research aims to apply the Certainty Factor algorithm in an expert system to detect stunting using the Case-Based Reasoning Method. The application of the CF algorithm by utilizing expert judgment has successfully strengthened the CBR method steps by calculating the similarity level. The results of the User Acceptance Test by 25 respondents showed an approval rate of 85%. If interpreted using the user approval range, these results are 81% - 100%, with a very high level of agreement. Based on calculating risky and safe stunting example cases, the CBR Method shows a similarity rate of 29.26% and 70.73%, respectively. Furthermore, safe stunting cases were analyzed using the CF algorithm with a confidence ratio of 91%.